(untitled) (Journal of Preventive and Social Medicine, 2023)
Background: Information on the extent of COVID-19 reinfection and associated risk factors is scarce in Bangladesh. The present study aimed to determine the prevalence, severity, and associated risk factors of COVID- 19 reinfection. Methods: This countrywide cross-sectional study targeted all COVID-19 patients reported in May 2021 at the Health Information Unit (HIU), Directorate General of Health Services (DGHS), Bangladesh. The study identified 242 re-infected cases among 41408 confirmed COVID-19 patients by reviewing the medical records at HIU, and DGHS. Considering the selection criteria and informed consent, we enrolled 202 re-infected patients. Data were collected through telephone interviews and reviewing medical records using a semi-structured questionnaire and a checklist. Results: The prevalence of COVID-19 reinfection was 0.58%, and most (98.0%) of them were urban residents. Of all, 37.1% had an interval of 3-6 months between two attacks of infections. The severity of reinfection included asymptomatic (6.4%), mild (67.8%), moderate (22.3%), and severe (3.5%) infections. The moderate and severe (25.9% and 7.4%) illness were significantly (p<0.001) higher in the patients having an interval of <3 months between two attacks. The moderate and severe illnesses (73.7% and 5.3%) were significantly (p<0.001) higher among the patients who didn’t maintain social distance. The patients aged 30-39 years had more chance of having mild (AOR=9.26, p=0.009) and moderate (AOR=16.58, p=0.008) infection. Conclusion: To avert COVID-19 reinfection and its severity, patients should be vigilant about preventive practices even after recovery. The study suggests effective interventions aligned with exposure, physical distancing, vaccination, and comorbidities to mitigate COVID-19 reinfection. JOPSOM 2021; 41(1):8-18